Shaping a valued learning journey: Student satisfaction with learning in undergraduate nursing programs, a grounded theory study. (May 2018) - Smith, Morgan R.; Grealish, Laurie; Henderson, Saras
Abstract: Background: Student satisfaction is a quality measure of increasing importance in undergraduate programs, including nursing programs. To date theories of student satisfaction have focused primarily on students' perceptions of the educational environment rather than their perceptions of learning. Understanding how students determine satisfaction with learning is necessary to facilitate student learning across a range of educational contexts and meet the expectations of diverse stakeholders. Objectives: To understand undergraduate nursing students' satisfaction with learning. Design: Constructivist grounded theory methodology was used to identify how nursing students determined satisfaction with learning. Settings: Two large, multi-campus, nursing schools in Australia. Participants: Seventeen demographically diverse undergraduate nursing students studying different stages of a three year program participated in the study. Methods: Twenty nine semi-structured interviews were conducted. Students were invited to describe situations where they had been satisfied or dissatisfied with their learning. A constructivist grounded theory approach was used to analyse the data. Results: Students are satisfied with learning when they shape a valued learning journey that accommodates social contexts of self, university and nursing workplace. The theory has three phases. Phase 1 - orienting self to valued learning in the pedagogical landscape; phase 2 - engaging with valued learning experiences across diverse pedagogical terrain; and phase 3 - recognising valued achievement along the way. Conclusion: When students experience a valued learning journey they are satisfied with their learning. Student satisfaction with learning is unique to the individual, changes over time and maybe transient or sustained, mild or intense. Finding from the research indicate areas where nurse academics may facilitate satisfaction with learning in undergraduate nursing programs while mindful of the expectations of other stakeholders such as the university, nurse registering authorities, employers and the receivers of nursing care.